Dynamic damage assessment of resistance spot welding for dissimilar plates by using model updating approach - Nazrotul Afina, Nazri (2019)
Top hat plate structure was fabricated in this study to represent floor pan compartment of body in white (BIW) structure, by using two dissimilar materials which are mild steel and stainless steel that were joined together through resistance spot weld (RSW) process. Objectives of this study were to determine and compare modal properties of RSW between dissimilar materials using FEA and EMA approaches, to minimize the discrepancies between FEA and EMA using sensitivity analysis, model updating procedure and lastly, to evaluate the damage assessment of RSW through experiment and simulation study. The tested structure was designed in CAD software, and normal mode analysis of FEA using MSC Nastran Patran was performed to find modal parameter along with modal testing using impact hammer with roving accelerometer method which was carried on to the specimen by having 50 measurement points. This study was continued with joining strategy analysis by applying Rigid Body Element (RBE), Bar Element (CBAR), Weld Element (CWELD) and Beam Element (CBEAM) at the real spot weld connection and their results were compared with EMA. After finding the most reliable joining strategy, model updating was conducted to reduce discrepancies between FEA joining and EMA. At the end, damage was introduced on both intact FEA and EMA structure and any changes in modal parameters were observed by removing four spot welds at the edge of tested structure. From the analysis, CWELD has been found as the most reliable joining to represent RSW connection and for sensitivity analysis, Young’s Modulus and density for both mild steel and stainless steel were selected for model updating, which was successfully performed on this joining. For damages study, it was observed that the value of natural frequencies has significant decrement after the damage was rendered in both FEA and EMA studies, which also resulted in a shift of frequency to a lower value in FRF graph. As the conclusion, CWELD was the most suitable joining to represent RSW and the presence of damage reduced natural frequency values which affected the modal properties of a structure.